(untitled) (Journal of Naval Architecture and Marine Engineering, 2020)
Inclined shaft propeller arrangements are demonstrated in the high-speed boat. The flow field around the propeller blades with inclined shaft propeller is unsteady due to the cross-flow component from the influx of the shaft direction which complicated more than the straight shaft propeller condition (without inclined shaft propeller). Therefore, realistic flow around inclined shaft propeller is important to the actual efficiency of propeller. In addition, propeller characteristics such as the pitch, skew and rake are influences to propeller performance, maybe not done in design condition which is different from the straight shaft propeller. This paper offers the investigation of unsteady propeller performance with operating the different inclined shaft angle conditions for Long-Tail Boat (LTB) using a Reynolds Averaged Navier-Stokes (RANS) solver. The unsteady calculations are conducted by inclined flow conditions. The computational results of propeller performance and pressure distribution on the suction and pressure sides at the blades of time-accuracy have been compared to each other including the wake effect behind the propeller. The results can be applied to adjust the inclined shaft angle of the boat.